Species-Dependent Response of Brassica chinensis L. to Elevated CO2 Gradients Influences Uptake and Utilization of Soil Nitrogen, Phosphorus and Potassium - Songmei Shi; Xinju Wang; Huakang Li; Jiajun Song; Xinhua He; Zhengan Yang (Agronomy, 2024)
Employing elevated CO2 (eCO2), similar to increasing atmospheric CO2 in a greenhouse, is a common practice used to increase vegetable crop yields. However, the responses of nutrient availability, nutrient uptake and use efficiency in leafy vegetables to eCO2 remain largely unknown. The plant biomass production, nitrogen (N), phosphorus (P) and potassium (K) contents, nutrient uptake, and soil enzymatic activities of three Brassica chinensis varieties of ‘Longpangqing’, ‘Heimeiren’ and ‘Qingjiangbai’ were thus assessed under ambient CO2 (C0, 420/470 ppm, day/night) and eCO2 (C1, C0 + 33.3%C0; C2, C0 + 66.7%C0; and C3, C0 + 100%C0) for 4 months. Biomass production was significantly enhanced in these three tested B. chinensis varieties along with eCO2 gradients, with the highest biomass production under C3. Moreover, the eCO2 significantly increased plant N and K uptake, P and K use efficiency, soil saccharase, urease, and phosphatase activities, but decreased plant P content, soil available N and K, and catalase activity. Under eCO2, ‘Qingjiangbai’ exhibited higher biomass production and P and K uptake, without a decrease in soil available N and P. Consequently, more external fertilizer supplementation (especially N, followed by K) is required to maintain or promote Brassica chinensis yield under eCO2, while these management strategies must be carefully considered for different crop varieties.